Preliminary study of community-acquired Staphylococcus aureus infection in Manaus Hospital, Amazonia Region, Brazil - Jesus M. Egido; Marcus L. Barros (Revista da Sociedade Brasileira de Medicina Tropical, 2003)
Methicillin resistant Staphylococcus aureus is considered a public health problem with a strong potential for dissemination and high rates of morbidity and mortality. In this study we describe bacteriological and epidemiological characteristics of Staphylococcus aureus in Manaus (Amazon region). During the one-year study period (2000-2001), sixteen cases of acute pyogenic multiple abscess were evaluated. Community-acquired S. aureus was identified as causative agent in 10 (62.5%) patients. The strains tested with antimicrobials by discs diffusion method, exhibited a high rate of sensitivity to cephalexin (100%), erythromycin (90%). Oxacillin-susceptible Staphylococcus aureus was 90%. No isolate was resistant to Vancomycin. To our knowledge, no series of community-acquired Staphylococcus aureus in Manaus hospital has been published. Our partial results showed a high rate of antimicrobial sensitivity among community-acquired Staphylococcus aureus in the hospital of Tropical Medicine Institute of Manaus, Amazon Region.